Cross-correlation between cosmological and astrophysical datasets: the Planck and Herschel case. Issue Volume 10:Issue S306(2014) (1st July 2015) - Bianchini, Federico; Lapi, Andrea
Abstract: We present the first measurement of the correlation between the map of the CMB lensing potential derived from the Planck nominal mission data and z ≳ 1.5 galaxies detected by Herschel -ATLAS (H-ATLAS) survey covering about 550 deg 2 . We detect the cross-power spectrum with a significance of ∼ 8.5σ, ruling out the absence of correlation at 9σ. We check detection with a number of null tests. The amplitude of cross-correlation and the galaxy bias are estimated using joint analysis of the cross-power spectrum and the galaxy survey auto-spectrum, which allows to break degeneracy between these parameters. The estimated galaxy bias is consistent with previous estimates of the bias for the H-ATLAS data, while the cross-correlation amplitude is higher than expected for a ΛCDM model. The content of this work is to appear in a forthcoming paper Bianchini, et al . (2014 ).